Clear cell sarcoma of the kidney: Patients' characteristics and improved outcome in developing countries. Issue 12 (31st August 2014) - Zekri, Wael; Alfaar, Ahmad Samir; Yehia, Dina; Elshafie, Maged M.; Zaghloul, Mohamed Saad; El‐Kinaai, Naglaa; Taha, Hala; Refaat, Amal; Younes, Alaa A.
<x xml:space="preserve">Abstract</x> Background Clear cell sarcoma of the kidney (CCSK) is a rare and aggressive tumor accounting for 5% of pediatric renal tumors with an incidence of 20 patients per year in the USA. It is bone metastasizing with poor prognosis. Our aim was to show characteristics of patients in relation to improved outcome in one of the developing countries. Procedure We included all patients diagnosed as CCSK in the period between July 2007 and March 2012 at Children's Cancer Hospital, Egypt. Patients' demographics, clinical presentation, pathology, and management were reviewed. Follow up was continued until April 2013. Results Twenty‐five patients were identified in the defined time interval, accounting for 7% all renal tumors diagnosed at the hospital. Mean age was 36 months. Abdominal swelling and hematuria were the most common presentations. Stages I, II, III, IV, and V represented 9 (36%), 3 (12%), 8 (32%), 3 (12%), and 2 (8%), respectively. Twenty‐four patients had radical nephrectomy either upfront or after neo‐adjuvant chemotherapy. Surgery was followed by adjuvant chemotherapy. Abdominal radiotherapy was given for local stages II and III. Twenty‐two patients reached complete remission, while one patient had stationary disease and two patients died due to progression and relapse. Overall survival was 88.5% and event‐free survival was 87.8% at 45 months. Conclusion Although previous studies indicate poor prognosis of CCSK, our experience shows that those patients can be treated using extensive chemotherapy combined with proper local control. Pediatr Blood Cancer 2014;61:2185–2190. © 2014 Wiley Periodicals, Inc.